First Report of Damping-Off on Strawberry Tree Caused by Colletotrichum acutatum and C. simmondsii in Italy - Polizzi, G (Plant disease, 2011)
In June 2010, a widespread damping-off was noticed in a commercial nursery in eastern Sicily on ~20,000 potted 2-month-old strawberry tree (Arbutus unedo L.) seedlings. More than 40% of the seedlings showed disease symptoms including brown lesions at the seedling crown above and below the soil line that expanded rapidly to girdle the stem. Stem lesions were followed by death of the entire seedling in a few days. Diseased stem and crown tissues of 20 seedlings were surface disinfested for 2 min in 1% NaOCl, rinsed in sterile water, plated on potato dextrose agar amended with 100 mg/liter of streptomycin sulfate, and incubated at 25°C in the dark. Fungal isolates with mycelial and morphological characteristics of Colletotrichum spp. were isolated from all seedlings. Fungal colonies were pale orange or gray without carmine pigments. On carnation leaf agar (CLA), single-spore isolates produced many orange masses of hyaline, aseptate conidia with a cylindrical to ellipsoidal shape, rounded apex, and 11 to 15 μm long and 3 to 4.5 μm wide (average 13.2 × 3.7 μm). The pointed conidia of 10 isolates were morphologically similar. DNA isolation was performed with the Wizard Magnetic DNA Purification Kit (Promega, Madison, WI) following the manufacturer's instructions with some modifications. A PCR assay was conducted on two representative isolates (ITEM 13492 and ITEM 13493) by analyzing sequences of gene benA (coding β-tubulin protein) using the primers T1 and T10 reported by O'Donnell and Cigelnik (1). BenA gene sequence of ITEM 13492 exhibited an identity of 99.8% to C. simmondsii strain BRIP 4704 (GenBank No. GU183277), while BenA gene sequence of ITEM 13493 exhibited an identity of 100% to C. acutatum strain BRIP52695 (GenBank No. GU183314). The identification of these two species was made by comparing the internal transcribed spacer region and BenA sequences of these two strains with that deposited by Shivas and Tan (2). Morphological characteristics, as well as the PCR assay, identified the isolates as Colletotrichum acutatum J.H. Simmonds and C. simmondsii R.G. Shivas & Y. P. Tan (2,3). Pathogenicity tests were carried out on 2-month-old seedlings of strawberry tree grown on alveolar trays. Conidial suspensions of two isolates (ITEM 13492 and ITEM 13493) were obtained from 14-day-old single-spore colonies on CLA, then adjusted to 105 conidia per ml and sprayed on seedlings. Fifty seedlings for each isolate were used. The same number of seedlings was mock inoculated with sterile distilled water. All seedlings were enclosed for 4 days in plastic bags and placed in a growth chamber at 24 ± 1°C for 45 days. Identical symptoms to those observed in the nurseries appeared 30 days after inoculation, and after 45 days, 80% of the plants were dead. No difference in virulence between the two isolates was observed and no symptoms were detected on the control plants. C. acutatum and C. simmondsii were successfully reisolated from all symptomatic tissues and identified as previously described, completing Koch's postulates. To our knowledge, this is the first report in the world of C. acutatum and C. simmondsii on strawberry tree. This suggests that Colletotrichum spp. may be important pathogens of young seedlings of strawberry tree in nurseries. References: (1) K. O'Donnell and E. Cigelnik. Mol. Phylo. Evol. 7:103, 1997. (2) R. G. Shivas and Y. P. Tan. Fungal Divers. 39:111, 2009. (3) B. C. Sutton. Page 523 in: The Coelomycetes. Commonwealth Mycological Institute, Kew, Surrey, England, 1980